Associations of human gene EPB41L3 DNA methylation and cervical intraepithelial neoplasia in women living with HIV-1 in Africa. (24th September 2018) - Kelly, Helen A.; Chikandiwa, Admire; Warman, Rhian; Segondy, Michel; Sawadogo, Bernard; Vasiljevic, Natasa; Didelot, Marie-Noelle; Meda, Nicolas; Weiss, Helen A.; Delany-Moretlwe, Sinead; Mayaud, Philippe; Lorincz, Attila
Abstract : Objectives: To evaluate associations of DNA methylation of the human tumour suppressor gene EPB41L3 with high-grade cervical intraepithelial neoplasia (CIN2+) and HIV-related factors among women living with HIV-1 (WLHIV) in Burkina Faso and South Africa. Design: Case–control study of WLHIV aged 25–50 with histology-determined CIN2+ (cases, N  = 152) and ⩽CIN1 (controls, N  = 210). Methods: EPB41L3 methylation was measured by pyrosequencing of bisulphite converted DNA from exfoliated cervical specimens at baseline and 16 months later. Median methylation levels were compared across CIN grades using the Mann–Whitney test and Cuzick test for trend. EPB41L3 methylation levels were dichotomized into 'high' and 'low' using the 66.7 percentile point of the distribution in the controls. Associations of EPB41L3 methylation with HIV-related factors were estimated by logistic regression. Results: Among 94 WLHIV in Burkina Faso and 268 in South Africa, median methylation levels at baseline for EPB41L3 increased with increasing CIN grade in both countries ( P -trend <0.001). 'High' methylation was more frequent among women with a longer time since HIV diagnosis in Burkina Faso [>5 years vs. ⩽5 years; adjusted odds ratio (aOR) = 4.15, 95% CI 1.09–15.83, adjusted for age, CD4 + count, high-risk HPV and CIN status], with low CD4 + count in both countries (CD4 + ⩽200 vs. ≥350 cells/μl: aOR = 7.14, 95% CI 1.44–35.37 in Burkina Faso; aOR = 2.55, 95% CI 1.07–6.07 in South Africa), and with prolonged ART use in South Africa (ART >2 years vs. ART-naïve: aOR = 2.40, 95% CI: 1.23–4.69). Conclusion: Methylation of EPB41L3 DNA is elevated among WLHIV with CIN2+ and independently associated with lower CD4 + count and ART use. Abstract : Supplemental Digital Content is available in the text